Digital wallets: a study on the influence of consumer perceptions and attitudes on impulsive consumer behaviour - Underdown, Kit; Tamara, Dewi (Frontiers in Human Dynamics, 2025)
Digital wallets, or electronic wallets (e-wallets), have developed to be the most common form of digital payment methodology in Indonesia in line with the significant growth in internet accessibility and adoption of financial technology (fintech). Accordingly, there has been a corresponding increase in research into the adoption, use, and impact of digital wallets. However, contemporary research has focused disproportionately on the positive outcomes of digital wallet use, with limited exploration of the potential negative consequences. The objectives of this study were to understand the relationship between digital wallet use and impulsive spending behaviour of consumers by examining the effect of perceived ease of use (PEOU), perceived enjoyment (PE) and perceived usefulness (PU) towards the impulsive behaviour (IB) with consumer attitude (CA) as a mediating variable. This study used convenience sampling to obtain data from 238 active digital wallet users residing in the DKI Jakarta area aged between 18 and 41. Results demonstrated that PE and PU had significant and positive impacts on CA, while PEOU did not. Further, CA did not have a significant influence on the dependent variable of IB. The research model accounted for 71% of the variance in CA, and 5.4% of the variance in IB. Results demonstrated there was no significant effect from consumer attitude as a mediator. The outcomes indicate the research model adequately and substantially explained the impact on the mediator consumer attitude; however, do not adequately explain impulsive behaviour. This research will contribute to the growing body of literature exploring the spectrum of outcomes of digital wallet use and inform the readership on the importance of perceived enjoyment and perceived usefulness of digital wallet use in driving consumer attitude.